Unified WiMAX network design with service optimisation. (29th June 2011) - Teterin, Vitaly; Hurley, Steve; Allen, Stuart M.
This paper presents an automated framework for the operational planning of WiMax networks. The framework consists of a cell planning (network design) algorithm that selects and fully configures base station sites, together with an automatic frequency planning algorithm for assigning subchannels in an OFDMA scheme. Results are presented, which indicate that it is preferable to include the frequency planning directly in the cell planning process rather design the network and subsequently assign subchannels.